1983
DOI: 10.1128/mcb.3.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a BALB/c-3T3 cell protein modulated by platelet-derived growth factor.

Abstract: The platelet-derived growth factor (PDGF) stimulates density-arrested BALB/c-3T3 cells to synthesize a protein (pII; Mr, 35,000) that is constitutively synthesized by spontaneously transformed BALB/c-3T3 (ST2-3T3) cells which do not require PDGF for growth. Antisera against a major excreted protein family (MEP) of retrovirus-transformed cells quantitatively precipitated cellular pII. PDGF-stimulated pII has the same molecular weight, a similar charge, and similar antigenic determinants as authentic MEP isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
43
0

Year Published

1985
1985
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…In this way the protooncogenes c-fos and c-myc have been found to be activated in a variety of cells (7)(8)(9)(10), as have a number of other genes for which probes are available. Altered expression of other specific genes has been inferred by the appearance of new proteins (11)(12)(13)(14) or translatable mRNAs (15) after growth stimulation. A more general way to identify genes activated by mitogenic stimuli is by differential screening of cDNA libraries prepared from RNA of resting cells exposed to serum or growth factors (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…In this way the protooncogenes c-fos and c-myc have been found to be activated in a variety of cells (7)(8)(9)(10), as have a number of other genes for which probes are available. Altered expression of other specific genes has been inferred by the appearance of new proteins (11)(12)(13)(14) or translatable mRNAs (15) after growth stimulation. A more general way to identify genes activated by mitogenic stimuli is by differential screening of cDNA libraries prepared from RNA of resting cells exposed to serum or growth factors (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…These growth factors found in plasma, which stimulate competent cells to replicate, have been identified (53,59,60) as somatomedin (65) and epidermal growth factor (5). In addition, it has been reported that the concentration of PDGF required to stimulate MEP synthesis maximally is less than that required to stimulate DNA synthesis in the presence of growth factors found in plasma (52). Hence MEP, potentially a necessary intermediary in PDGF-induced competence, is not a sufficient mediator (52).…”
mentioning
confidence: 99%
“…Two additional growth-promoting agents, 12-O-tetradecanoyl phorbol-13-acetate (TPA) (19) and platelet-derived growth factor (PDGF) (52,53), considerably enhance both the levels of synthesis and the secretion of MEP in nontransformed cells. An understanding of the means by which growth-promoting agents such as TPA and PDGF enhance the synthesis of MEP would doubtless provide insight into the mechanisms of the broad range of phenotypic alterations induced by these agents (20,52).…”
mentioning
confidence: 99%
See 2 more Smart Citations